2023
DOI: 10.1177/00405175221150650
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental research of fiber motion in vortex spinning

Abstract: The application of high speed air flow in the textile field represents the frontier development direction in this field. However, the coupling mechanism between air flow and fiber is extremely complicated which greatly limits the development and application of new textile technologies. For this reason, this research study is intended to focus on the common cutting-edge basic scientific problem of the air-flow-fiber coupling mechanism, the vortex spinning technology is taken as a breakthrough point for research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The main function of the vortex field in the textile process is twisting yarns, which is used in vortex spinning 1 and rotor spinning, 2 but some tiny vortices are not conducive for yarn orientation. The jet field has critical functions in fiber web forming and guiding yarn movement, and is widely used in air jet looms weft insertion, 3 electrostatic spinning, 4 melt blown spinning, 5 and spunbond processes.…”
mentioning
confidence: 99%
“…The main function of the vortex field in the textile process is twisting yarns, which is used in vortex spinning 1 and rotor spinning, 2 but some tiny vortices are not conducive for yarn orientation. The jet field has critical functions in fiber web forming and guiding yarn movement, and is widely used in air jet looms weft insertion, 3 electrostatic spinning, 4 melt blown spinning, 5 and spunbond processes.…”
mentioning
confidence: 99%
“…Shang et al 1 verified that the turbulence generated during the normal spinning process is much more pronounced than at the beginning of spinning by analyzing the three-dimensional numerical simulation of airflow characteristics, which is conducive to the stabilization of the spinning process and the improvement of yarn strength. Shang et al 2 developed a three-dimensional numerical model of airflow within a vortex spinning nozzle and a free-end fiber, utilized structured hexahedral meshes and unstructured tetrahedral structures to delineate the computational region of the airflow and verified the importance of dynamic numerical simulation in solving the unobservable dynamic torsion process by taking into account the physical properties of the fiber. Pei and He 3 utilized a charge-coupled device in conjunction with an industrial endoscope to observe the formation process of a copper wire core yarn and theoretically demonstrated that this method can be applied to other textile manufacturing processes.…”
mentioning
confidence: 99%